Comprehensive analysis of methods for estimating actual paddy evapotranspiration—A review - Behura, Kiran Bala; Raul, Sanjay Kumar; Paul, Jagadish Chandra; Mohanty, Sheelabhadra; Jena, Prachi Pratyasha; Dwibedi, Sanat Kumar; Ghosh, Subhankar; Singh, Laishram Kanta; Devi, Sougrakpam Roma; Singha, Arun Kumar; Mohanty, Amulya Kumar (Frontiers in Water, 2025)
Evapotranspiration (ET) has considerable significance in the water cycle, especially in farming areas where it determines crop water needs, irrigation plans, and sustainable management of water resources. This study stresses the need for accurate ET estimation in paddy fields where rice is grown because of its high-water sensitivity and consumption which has implications for water use efficiency and food security. The study attempts to address the problem by estimating rice ET: Standard procedures such as the Penman–Monteith equation, lysimeters, and even remote sensing procedures such as Surface Energy Balance Algorithm for Land (SEBAL) and Mapping Evapotranspiration at High Resolution with Internalized Calibration (METRIC) are all investigated. Furthermore, an attempt is made to combine remote sensing data with machine learning techniques for refined ET estimation. Utilizing modernized technologies and hybrid models, the research investigation aims to deepen the understanding of ET variability for rice cropping systems to promote improved water resources management and sustainable agriculture practices as areas for future work suggest the application of vegetation indices incorporating high-resolution multi-spectral imagery to accurately estimate ET and appropriately differentiate between evaporation and transpiration in these complex agricultural systems.